Effective Taxation for Recipients of Social Assistance in Germany and the Consequences of the 1996 Tax Reform - Thimann, Christian (IMF Working Papers; Working Paper, 1995)
This paper explores the problem of effective taxation at the lower end of the income scale in Germany. For the recipients of social income maintenance--currently about 1.8 million nationals--effective taxation consists not only of the explicit taxation through the tax code but also of the implicit taxation through the withdrawal of benefits. The paper calculates effective tax rates for recipients of social assistance; it is shown that for labor incomes in the lower income range explicit and implicit taxation add up to a marginal burden of just under 75 percent on average. The 1996 tax reform alleviates the explicit tax burden on low incomes, but it does not alleviate the total marginal burden on labor earnings of welfare recipients. It increases net incomes, but since the withdrawal of benefits increases with net incomes, too, the overall burden remains practically unchanged. Therefore, effective welfare traps remain prevalent; these could only be avoided through a reform of the system of social assistance and withdrawal. Constraints and possible steps for reform are discussed.